Semiotics of Synthetic Media - Bassano, Giuditta; McIntyre, Andrew; Polidoro, Piero (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
This chapter proposes a dual framework for interpreting synthetic media by coupling generative semiotics (enunciation, plastic/figurative isotopies, anchorage, uncanny cues) with Actor-Network Theory (ANT) mapping of production, circulation, and reception. We first situate synthetic images within longer genealogies of manipulation while stressing contemporary discontinuities in scale, speed, access, and political stakes. We then articulate how meaning emerges at two levels: internal textual organization and the socio-technical networks of datasets, models, platforms, policies, and audiences. Four case studies (satire/meme, advertising resurrection, televisual “interview,” participatory grotesque) demonstrate how contracts of veridiction shift across genres and contexts. Finally, we introduce a semiotically grounded taxonomy and a reception matrix oriented to political prevention and media-education strategies, privileging capacity-building over mere detection.